Assessing the Maize (Zea mays L.) Crop Performance Using Spectral Indices under Different Sowing Dates and Irrigations Schedules - Pallavi, Ch.; Sreenivas, G.; Yakadri, M.; Biswal, Anima; Madhavi, A.; Sreekanth, P. D.; Laxman, B. (International Journal of Bio-resource and Stress Management, 2021)
Field experiment was conducted at ARI, PJTSAU, Hyderabad with four dates of sowing (18th June, 04th July, 19th July and 03rd August in Kharif, 2016 and 01st November, 18th November, 01st December and 17th December in rabi, 2016–17) as main plots and four irrigations regimes (Control, 0.4 IW/CPE, 0.6 IW/CPE and 0.8 IW/CPE in kharif and 0.4 IW/CPE, 0.6 IW/CPE, 0.8 IW/CPE and 1.0 IW/CPE in rabi) as sub-plots in split plot design replicated thrice. Scheduling irrigation at unstressed conditions, 0.8 IW/CPE (I3) and 1.0 IW/CPE (I4) of maize resulted in low reflectance in visible region (400 to 700 nm) and mid infrared (MIR) region (1350–2500 nm) and high in near infrared (NIR) region (700 to 1350 nm) during kharif and rabi respectively. While, under stressed condition, the reflectance was high in visible and MIR region and low in NIR region in rainfed and 0.4 IW/CPE (I0) respectively in kharif and rabi. Significantly higher drymatter, LAI and grain yield was observed in 04th July (D2) and 01st November (D1) sown crop in kharif and rabi respectively. However, spectral indices (SR, PRI, NDWI at 1240, 1640 and 2130 nm, NDII, NMDI, WBI and SWRI) was attained by 18th June (D1) and 01st November (D1) during kharif and rabi respectively. Higher drymatter, LAI, grain yield and spectral indices was recorded with I3 (0.8 IW/CPE) and I4 (1.0 IW/CPE) in kharif and rabi respectively. All the spectral vegetation indices correlated positively with LAI, drymatter and grain yield.